Love Thy Neighbour? Brexit and Hate Crime - Joel Carr; Joanna Clifton-Sprigg; Jonathan James; Suncica Vujic (Institute of Labor Economics (IZA), 2020)
We provide causal evidence of the impact of the Brexit referendum vote on hate crime in the United Kingdom (UK). Using various data sources, including unique data collected from the UK Police Forces by Freedom of Information (FOI) requests, and various estimation methods (difference-in-differences, event-study analysis and synthetic control methods), we find that the Brexit referendum led to an increase in hate crime by around 15-25%. This effect was concentrated in the first quarter after the referendum and was larger in areas that voted to leave the European Union (EU). We also provide evidence against the hypotheses that this was due to victims' greater willingness to report crimes or due to changes in police behaviour and perceptions of the victims. We also present suggestive evidence that the media and social media played a small but significant role in the increase in hate crime.
Keywords: D72; J15; K42; 330; hate crime; referendum vote; Brexit; synthetic control method